Introduzione. Scuola e salute mentale: un ponte da costruire - Masillo, Alice; Lo Cascio, Nella; Brandizzi, Martina; Monducci, Elena (Il sogno della farfalla, 2018)
The article introduces a monographic issue on education whilst explaining reasons behind this choice. The project stems from the need, which is extensively shared, to set up a network between mental health operators and teachers so as to carry out efficacious preventive interventions. In fact, teachers stand in a privileged position when it comes to observe the youths, adolescents in particular. It is well known that onset of most mental illnesses occurs between the first phases of adolescence and early adulthood, and mental illnesses are one of the main causes of mortality and morbidity amongst the youths. This phase of life is crucial as it is a relevant transition period. The main challenge for those who want to prevent onset of psychiatric disorders is therefore distinguishing physiological crises due to this period of changes from the first signs of a mental illness. Sections and articles in this issue move from thinking how, in order to achieve primary prevention, correct information and education on mental illness is needed. They also move from the idea on human beings which was theorized by Massimo Fagioli more than fifty years ago. According to this idea, and differently from what put forth by dominant western culture, which has a religious and rational core, human beings are born healthy, in their minds and bodies, and their non-conscious reality, which is made of affections and images, is at the basis of the fulfilment of human identity; it is not “evil” or “animality” which must be hindered or controlled.